Grand theft Sandton: political corruption and corporate crime as South African capitalism - Bond, Patrick (Capitalism and economic crime in Africa, 2024)
What do economic crime and fraud really represent in contemporary South Africa? The typical analysis of corruption is limited to blaming individual political leaders or managers of state departments and parastatal corporations. The private sector is usually mentioned insofar as either Black Economic Empowerment (BEE) in part relies upon the post-apartheid government’s procurement system and corporate ownership-sharing patronage, or ‘Illicit Financial Flows’ that are understood to be rampant, along with a high degree of market concentration in areas such as currency trading, mega-project construction and other sites of price and conduct collusion. But more cases of economic fraud and criminality are now visible, in part thanks to courageous whistle-blowers (Uys 2022; Radulovic 2023), investigative journalists (e.g., AmaBhungane and the Organized Crime and Corruption Reporting Project), political advocates abroad (e.g., Lord Peter Hain), corruption-watchdog NGOs (e.g., Open Secrets 2023), scholars (e.g., Chipkin and Swilling 2018; Gelb 2023), and the U.S. Foreign Corrupt Practices Act (FCPA) when used against South Africa. In March 2024, imminent prosecution of the highest-profile corporate crime case - the Steinhoff accounting swindle which cost the firm’s investors $10 billion - threatened former chief executive Markus Jooste to the point asset confiscation loomed and catalysed his suicide. Similarly, the collapse of corrupt private empires led to apparent suicides by Bosasa’s Gavin Watson in 2019 and Johannesburg Consolidated Investment’s Brett Kebble in 2005 - both high-profile supporters of (and prolific donors to) the ruling African National Congress (ANC).